Electroacupuncture Promotes Central Nervous System‐Dependent Release of Mesenchymal Stem Cells. (25th April 2017) - Salazar, Tatiana E.; Richardson, Matthew R.; Beli, Eleni; Ripsch, Matthew S.; George, John; Kim, Youngsook; Duan, Yaqian; Moldovan, Leni; Yan, Yuanqing; Bhatwadekar, Ashay; Jadhav, Vaishnavi; Smith, Jared A.; et al.
Abstract : Electroacupuncture (EA) performed in rats and humans using limb acupuncture sites, LI‐4 and LI‐11, and GV‐14 and GV‐20 (humans) and Bai‐hui (rats) increased functional connectivity between the anterior hypothalamus and the amygdala and mobilized mesenchymal stem cells (MSCs) into the systemic circulation. In human subjects, the source of the MSC was found to be primarily adipose tissue, whereas in rodents the tissue sources were considered more heterogeneous. Pharmacological disinhibition of rat hypothalamus enhanced sympathetic nervous system (SNS) activation and similarly resulted in a release of MSC into the circulation. EA‐mediated SNS activation was further supported by browning of white adipose tissue in rats. EA treatment of rats undergoing partial rupture of the Achilles tendon resulted in reduced mechanical hyperalgesia, increased serum interleukin‐10 levels and tendon remodeling, effects blocked in propranolol‐treated rodents. To distinguish the afferent role of the peripheral nervous system, phosphoinositide‐interacting regulator of transient receptor potential channels (Pirt)‐GCaMP3 (genetically encoded calcium sensor) mice were treated with EA acupuncture points, ST‐36 and LIV‐3, and GV‐14 and Bai‐hui and resulted in a rapid activation of primary sensory neurons. EA activated sensory ganglia and SNS centers to mediate the release of MSC that can enhance tissue repair, increase anti‐inflammatory cytokine production and provide pronounced analgesic relief. Stem Cells 2017;35:1303–1315 Abstract : Acupuncture is among the oldest healing practices in the world and is currently one of the most rapidly growing complementary therapies. Our studies provides strong support for the use of electro acupuncture at specific immune points to stimulate mesenchymal stem cell (MSC) and macrophage release into peripheral blood through hypothalamic and sympathetic nervous system activation (SNS). We show using MRI and direct neurostimulation studies that EA at specific immune points results in SNS activation and the metabolically beneficial response of browning of white adipose fat. Electro acupuncture served to facilitate tissue repair following tendon injury by increasing type III collagen and by increasing levels of IL‐10. Our study supports that harvesting of MSC from the blood of EA‐ treated human subjects and ex vivo expansion is feasible and may serve as a practical method to harvest cells for autologous cell therapy, free of the risks and discomfort associated with current more invasive and toxic collection methods.